Ministry of Trade and Industry Decree No. 87 For The Year 2016 Regarding the Non Enforcement of the Export Rules on Certain Raw Materials Exported to the Free Zones = وزارة التجارة والصناعة قرار رقم 87 لسنة 2016 فى شأن عدم سريان القواعد التصديرية على بعض الخامات المصدرة إلى المناطق الحرة - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic